Substrate and fertigation management modulate microgreens production, quality and resource efficiency - Paglialunga, Gabriele; El Nakhel, Christophe; Proietti, Simona; Moscatello, Stefano; Battistelli, Alberto; Formisano, Luigi; Ciriello, Michele; Del Bianco, Marta; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Sustainable Food Systems, 2023)
Long-term space missions will require a self-sustaining food production system to meet the crew’s nutritional and health needs. For this purpose, plant-based food production systems with elevated resource efficiency are required, based on advanced agricultural technologies that produce phytonutrient-rich crops. In addition to the resource requirements for crop production on Earth, volume and time efficiency become essential factors to consider for food production in space. Microgreens represent a promising candidate for space farming as they have a high harvest index, short cultivation cycle, and high nutritional potential. However, the development of specific technical protocols for growing microgreens in space is essential since different agronomic inputs, such as substrates and fertigation, can modulate productivity, quality and resource efficiency of microgreens cultivation. The current work examines the effects of different substrates (coconut fiber and cellulose sponge) and nutrient solution (NS) management strategies (quarter strength Hoagland and half strength Hoagland/osmotic water) on the production of two species of microgreens [Raphanus sativus cv. Saxa 2 (Radish); Brassica oleracea var. capitata f. sabauda cv. Vertus (Savoy cabbage)]. The appraisal focused on (i) biomass production and quality, and (ii) sizing of space facilities devoted to the production of phytonutrients required for the astronauts’ wellbeing. In our study, the interaction among species, substrate and NS significantly affected the accumulation of fructose, sucrose, total soluble non-structural carbohydrates and nitrate as well as the daily production of total ascorbic acid and, in turn, the required microgreens serving to supply its adequate daily intake. Species-substrate interaction effects on fresh yield, dry yield, dry matter, anthocyanins, TPC, β-carotene and sulfate content as well as the cultivation surface required to produce the adequate daily intake of ascorbic acid (AscA) were assessed. Substrate-NS interaction modulated the anthocyanins, violaxanthin and sulfate contents independently of species. On the other hand, single factor effects were identified with respect to the accumulation of lutein, chlorophylls, glucose, and starch. Therefore, the management of microgreens cultivation in terms of NS and substrate is an effective tool to meet the phytochemical requirements of the crew.